TEACHING CHILDREN ETIQUETTE THE PLACE OF THE WISDOMS OF ALISHER NAVAI - Raximova Gulbaxor; Fayziyeva Shamsiya; Obidjonova Ruxshona (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article examines the role of Alisher Navoi’s wisdom in shaping the spirituality of the younger generation. Analyzes the metods of teaching Alisher Navoi’s wisdom in primary education.